THE TURKMEN ECONOMY: YEAR-END RETURNS FOR 2010 - PROKLOV, Igor (CENTRAL ASIA AND THE CAUCASUS, 2011)
The year 2010 rounded off many of the socioeconomic development programs adopted in Turkmenistan 10 years ago while Saparmurat Niyazov was still in power.1 Many observers were initially skeptical about the indices these programs produced since they seemed to present an exclusively rosy picture of the situation in the country. For example, according to the plan announced in 2001 by Minister of the Oil and Gas Industry and Mineral Resources K. Nazarov, Turkmenistan should have produced 120 bcm of gas and 48 million tons of oil in 2010, while exporting 100 bcm and 33 million tons, respectively. However, as the further data for 2010 show, the actual figures were much more modest, primarily due to the unfavorable market situation in recent years. All the same, the fact that such programs made it possible to formulate the main priorities and vectors of development, laying the foundation for perhaps not such rapid but nevertheless stable growth, should be given its due. Although the world crisis that began in 2008 did not directly affect Turkmenistan’s financial system and the country recovered from the crisis independently without any external financial support, the Turkmen leadership was nevertheless faced with the need to thoroughly re-examine its strategic plans. This primarily concerned adjusting the reference points in the country’s energy policy. The crisis clearly showed that placing exclusive priority on the export of energy resources was fraught with serious economic risks, not to mention the fact that it could well doom previously reached contracts and solemnly registered agreements to remain on paper. As we know, Turkmenistan owns large supplies of natural gas, so the choice the leadership made after the country acquired its independence of placing the main stakes on the fuel and energy complex as the driving force behind all the other branches of the national economy is entirely logical and justified. But it eventually became understood that the country’s large reserves of natural resources might not only be a great boon, but also an enormous bane, mainly for the country’s ordinary people. The potential profits from energy resource export should have made the country prosperous and raised the standard of living above the average, to say the least. According to the Turkmen leaders, only a few circumstances, which required the mobilization of both foreign and domestic policy efforts to overcome, prevented economic prosperity from being achieved. First, the existing gas- and oil-producing capacities had to be modernized, the old gas pipelines repaired, and new routes for delivering energy resources to potential consumers laid; and second, agreements had to be reached with the consumers themselves. As the events of the past two decades have shown, this was a far-from-easy task: solvent consumers are a long way off, while close neighbors are also rich in energy resources and ready to put up competition at the first opportunity. In these conditions, the Turkmen leaders (first Saparmurat Niyazov and then Gurbanguly Berdymukhammedov) were very well aware and are still well aware that only a sophisticated multi-vector energy policy and diversification of deliveries will make it possible for the country to draw closer to its designated goals. It cannot be denied that the strategy of diversification pursued has begun to bear fruit, and in the next decade the set tasks could be fully implemented. Despite the slump in the market, many world players are interested in strengthening their foothold in Turkmenistan’s energy industry. In so doing, its reluctance to become politically and economically dependent in new ways on more powerful players is prompting the country’s leadership to adopt what at times appear to be unusual ways of organizing public life and managing the national economy, which is often criticized by the world community.